2006
DOI: 10.1021/bi060245+
|View full text |Cite
|
Sign up to set email alerts
|

Juxtamembrane Protein Segments that Contribute to Recruitment of Cholesterol into Domains

Abstract: We investigated the properties of several peptides with sequences related to LWYIK, a segment found in the gp41 protein of HIV and believed to play a role in sequestering this protein to a cholesterol-rich domain in the membrane. This segment fulfills the requirements to be classified as a CRAC motif that has been suggested to predict those proteins that will partition into cholesterolrich regions of the membrane. All of the peptides were studied with the terminal amino and carboxyl groups blocked, i.e. as N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 34 publications
4
123
0
Order By: Relevance
“…28). Significant structural and operational differences, however, exist between the CDC cholesterol recognition motif and the CRAC motif.…”
Section: Discussionmentioning
confidence: 99%
“…28). Significant structural and operational differences, however, exist between the CDC cholesterol recognition motif and the CRAC motif.…”
Section: Discussionmentioning
confidence: 99%
“…One established sequence selective for binding cholesterol is the putative CRAC motif, first identified in the benzodiazepine receptor (43) and later identified in many other proteins and peptides (40,44,45). This motif is defined as a sequence pattern of -(Leu/Val-(X) 1-5 -Tyr-(X) 1-5 -Arg/Lys)-, in which (X) [1][2][3][4][5] represents between one and five residues of any amino acid (40,45). Cholesterol interacts with the CRAC motif with both attractive van der Waals interactions between hydrophobic surfaces and electrostatic interactions between the positively charged Arg or Lys residue and the cholesterol -OH group (40,45).…”
Section: Discussionmentioning
confidence: 99%
“…This motif is defined as a sequence pattern of -(Leu/Val-(X) 1-5 -Tyr-(X) 1-5 -Arg/Lys)-, in which (X) [1][2][3][4][5] represents between one and five residues of any amino acid (40,45). Cholesterol interacts with the CRAC motif with both attractive van der Waals interactions between hydrophobic surfaces and electrostatic interactions between the positively charged Arg or Lys residue and the cholesterol -OH group (40,45). In a study of a peptide from the fusogenic gp41 protein of HIV-1, Epand et al (40) found that the single Leu to Ile substitution in the CRAC motif (from LWYIK to IWYIK) resulted in no preferential interaction with cholesterol (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPER carboxy-terminal LWYIK sequence has been identified as a potential "cholesterol recognition/interaction amino acid consensus" (CRAC) domain functional in fusion [83][84][85][86][87]. Recently reported experimental evidence and modeling studies provide the physicochemical grounds for a direct interaction of MPER-CRAC with Chol [84,85,88,89]. MPER-Chol interaction would be based on two capacities of CRAC sequence, namely, wrapping and blocking of the interfacial cholesterol OH group by H-bond interactions, and stacking of aromatic side chains with A ring of cholesterol.…”
Section: Mper Structure-functionmentioning
confidence: 99%